Physical activity interventions in adult kidney transplant recipients: an updated systematic review and meta-analysis of randomised controlled trials - Bishop, N.; Billany, R.; Castle, Ellen; Graham-Brown, M.; Greenwood, S.; Lightfoot, C.; Wilkinson, T. (Taylor & Francis, 2025)
Background: Kidney transplant recipients (KTRs) exhibit a high prevalence of cardiovascular disease (CVD) and adverse changes in physical fitness and body composition. Post-transplant management recommends being physically active and evidence in this field is growing. The aim of this review was to update our previous systematic review and meta-analysis of randomized controlled trials (RCTs) assessing the effects of physical activity and exercise training interventions in KTRs.